FROZENSTORAGE CHARACTERISTICS OF CULTURED MACROBRACHIUM ROSENBERG/I (dE MAN) - BASU, S.; CHOUKSEY, M. K. (Journal of Indian Fisheries Association, 2016)
Cultured Macro brachium rosenbergii (Scampi, about 30 g each) in headless shell-on form was individually quick frozen in a spiral freezer. The frozen samples were glazed and packed in polythene bags, which were further pac{ed in master carton and stored at - 18 oc. Samples were drawn at regular intervals and subjected to biochemical, bacteriological and organoleptic analysis to study its storage characteristics. The data on the above parameters showed that the samples were in prime acceptable condition when stored upto 23 weeks. No appreciable change in colour and odour was noticed in the raw muscle. Mterwards, organoleptic evaluation of the cooked muscle revealed slight change in the flavour. Texture also appeared little tougher. These changes in organoleptic characters were well supported by the biochemical bacteriological changes in the muscle. Keywords : Storage characteristics, biochemical, bacterological organoloptic